Asymptomatic intracardiac mass in a 14-year-old girl with granulomatosis with polyangiitis: Case report - Harris Julia G; Salvay David M; Klein-Gitelman Marisa S (BMC, 2012)
Abstract Granulomatosis with polyangiitis (GPA; Wegener's granulomatosis) is a systemic necrotizing vasculitis of unknown etiology that commonly involves the upper airways, lungs, and kidneys. Cardiac involvement with an intracardiac mass is an exceedingly rare manifestation of this disease, especially in the pediatric population where, to our knowledge, only one article exists to date that has described such a finding. In this report, we present the case of an adolescent female who initially presented with renal failure and an intracardiac mass. Subsequent work-up led to a diagnosis of granulomatosis with polyangiitis (GPA). Cardiac manifestations in pediatric GPA are not common; however, they may be more prevalent than reported given recent adult literature and concern for clinically silent abnormalities.